IMPROVING STUDENTS ACHIEVEMENT IN WRITING DESCRIPTIVE TEXT THROUGH GROUP INVESTIGATION TECHNIQUE - Yetti Lestari and Sri Juriati Ownie (REGISTER: Journal of English Language Teaching of FBS-Unimed, 2014)
This study aims to improve students’ achievement in writing descriptive text through Group Investigation technique. This study was conducted by using classroom action research that has two cycles within. The first cycle was conducted in four meetings and the second cycle was conducted in two meetings. The subject of the research was the students of grade VIII at Yayasan Pendidikan El Hidayah Madrasah Tsanawiyah Desa Lalang Sunggal which consisted of 28 students. The instruments of collecting data were quantitative (writing test) and qualitative data (observation sheet, questionnaire sheet, and diary notes). Based on the writing test scores, students’ score kept improving in every test. In the orientation test the mean score was 59.42, in the first cycle, the mean score of the competence score was improved to be 68.17, in the second cycle; the mean of the competence score was also improved to be 76.85. Based on the observation sheet, questionnaire sheet, and diary notes, it was found that teaching-learning process ran well. Students were active, enthusiastic, and interested in writing. The result of the research showed that Group Investigation Technique could improve students’ achievement in writing descriptive text.